Pengaruh Investasi Dan Tenaga Kerja Terhadap Pertumbuhan Ekonomi Di Jember - Dasururi, Rubait; Dwiningwarni, S.S (eBA Journal: Journal Economics, Bussines and Accounting, 2016)
This research is intended to analyze the effect of investment and labor on the Gross Regional Domestic Product (GRDP) of Jember District during the period of 2001- 2010. This study is motivated by the facts that the Jember Gross Regional Domestic Product has been fluctuated and its value is far from other districts in East Java during the period study.  This study makes use of time series data of 2001-2010 and it utilizes regression analysis of “Ordinary Least Square (OLS)” and supporting software from SPSS 13. The findings of this study suggest that investment and labor do give a positive impact on the fluctuation of Jember GRDP. It is recommended that to increase GRDP of Jember, a policy is needed to motivate all parties to make investment in this region. The effort to increase investment should be focused on activities that involve many workers. Finally the role of regional government trough which is able to stimulate the increasing variable of private investment and the opportunity of labor force which is expected to increase the regional economic activities in order to reach the economic growth and people income per kapita.